A theory of emergency service command staff sensemaking processes - Bayer, Johannes Robert (Cranfield University, 2010)
Fire Service commanders work in a very dynamic environment. This research investigated the process they use to make sense and thereby develop understanding of situations during the response to a large-scale emergency. In previous research that investigated decision-making and situation awareness in real-life environments, the need for commanders to understand an incident is emphasised. This research aimed to generate new insights into the process individuals follow to build and improve situational understanding. An exploratory project phase was used to focus the research. Data from emergency exercises and interviews resulted in the design for the main study regarding application domain, data sources and methodological issues. For the main study, records of publicly available interviews with senior officers of the New York Fire Department on their experience of the response to the events at the World Trade Center on September, 11 2001 were analysed. Findings include six variations of the sensemaking process structure, which is characterised by distinct stages. A following investigation into why these stages occur took a theory-building approach and revealed two insights. First, process stages are tied to seven hierarchical but interlinked levels of understanding. Second, three groups of underlying mechanisms trigger process stages: four cognitive factors, eight needs to understand and three situational factors. The mechanisms occur in different combinations across process variations and have varying explanatory power. This study contributes to knowledge on the process of building and improving situational understanding and its link to understanding. A micro-level view of the sensemaking process is provided, showing the specific understanding that is gained and evolves along its stages. The view of sensemaking is extended from understanding what is going on and what can be done to include understanding performance of action. A review with experts revealed that findings adequately reflect the thinking of commanders during incident response and might have practical relevance for training and command support.
Keywords: Incident command; business continuity; cognitive processes; command training; understanding